SISA LEBIH PEMBIAYAAN ANGGARAN DAN DESENTRALISASI FISKAL TERHADAP BELANJA MODAL PEMERINTAH DAERAH KABUPATEN/KOTA DI JAWA BARAT - Neni Nurhayati (Program Studi Akuntansi, Universitas Kuningan, 2021)
The purpose of this research is to find out the effect of remaining more budget financing and fiscal decentralization on capital expenditure in districts/cities in the Region West Java period of 2015-2019. This research used secondary data in the form from Realized Local Government Budget obtained from Directorate General of Regional Fiscal Balance (DJPK).The population of this research is the report on government budget realization of districts/cities in West Java period of 2015-2019. All data is collected by sampling quota. The sample amounted to 105 financia report data. The analytical methods used in this research are the descriptive and statistic method of regression analysis of data panels including testing of hypotheses through F test, t-test and coefficient of determination (R2). The test model selection in this research is Fixed Effect. Based on the results of this research shows that remaining more budget financing and fiscal decentralization are simultaneously affecting capital expenditure. Partial remaining more budget financing variables and fiscal decentralization have a positive and significant impact on capital expenditure.Keywords: Remaining More Budget Financing, Fiscal Decentralization, , Capital Expenditure.